Acceptability of Rhizoma Peanut Forage by Horses and Its Benefits on Feeding Behavior - Carol Vasco; Jose Dubeux; Erick Santos; Carissa Wickens; Lori Warren (EDIS)
Rhizoma peanut hay has been demonstrated to benefit horses’ feeding behavior with reduced inactive time, which can result in lower risk for abnormal behaviors in stabled horses. This publication is intended to provide information to Extension agents, horse owners, and equine facility managers. Written by C. Vasco, J. Dubeux, E. Santos, C. Wickens, and L. Warren, and published by the UF/IFAS Department of Animal Sciences, October 2023.